Upper arm circumference measurement for detecting overweight and obesity in children aged 6-7 years - Dewi Rosariah Ayu; Aditiawati Aditiawati; Julius Anzar; Erial Bahar (Paediatrica Indonesiana, 2017)
Background Obesity is a worldwide problem and is associated with increased risk of metabolic syndrome. Nutritional status in children has traditionally been determined by body mass index (BMI) scores, but with limitations. Upper arm circumference measurement may be a better predictor of energy, protein, and fat storage, as well as a simpler method for screening overweight and obesity in children.Objective To determine the diagnostic value of upper arm circumference compared to BMI for detecting overweight and obesity in children aged 6-7 years.Methods This diagnostic study with a cross-sectional design was performed from September to October 2015 at 16 primary schools in Palembang, Indonesia. We measured the heights, weights, and upper arm circumferences, and calculated BMIs of 2,258 children. Receiver-operator characteristic (ROC) curve analysis was used to find an optimal upper arm circumference cut-off point to detect overweight and obesity. Diagnostic value was calculated by using a 2x2 table analysis.Results The prevalences of overweight and obesity were 5.8% and 11.7%, respectively. The optimal upper arm circumference cut-off points for detecting overweight in children aged 6-7 years was 185 mm (sensitivity 88.1% and specificity 78.3%), and for obesity was 195 mm (sensitivity 90.15% and specificity 86.65%). Upper arm circumference had a strong correlation with BMI.Conclusion Upper arm circumference measurement is an accurate method fordistinguishing between normoweight, overweight, and obesity in children aged 6-7 years.